Fatos da Igreja Historia da Vida dos Santos - Silva, Luiz Augusto Rebello (Em casa de A. J. F . Lopes, 1870)
Stamp, Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 18.Bookworm; 2.Damage